PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR PENDIDIKAN PANCASILA PADA PESERTA DIDIK KELAS VI SEKOLAH DASAR - Nurfajriani A. Tjaolo; Sri Mulyani Sabang; Asnaredin Manitu (LPPM Universitas Cipta Mandiri, 2025)
The results of observations made in class VI of SD Inpres 3 Tondo showed a problem in the form of a decrease in student interest in learning, especially in learning Pancasila and Citizenship Education (PPKn). This study aims to analyze the effectiveness of Wordwall media in increasing students' interest in learning Civics subjects in class VI SD Inpres 3 Tondo. The results of the comparison of student activity data in learning cycle 1 and cycle 2 of student activity show the results, indicators of participatory activity in using wordwall have a percentage in cycle 1 of 46.88% (15 students) increased in the cycle to 78.12% (25 people), active indicators in using wordwall in cycle 1 of 50% (16 people) increased in cycle 2 by 81.12% (26 students), activity indicators can use wordwall in cycle 1 by 40.62% (13 people) increased to 87.5% (28 students), activity indicators can answer quiz in wordwall in cycle 1 by 53.12% (17 people) in cycle 2 increased to 68.75% (22 people) and activity indicators happy / happy during the learning process in cycle 1 by 62.5% (20 people) increased in cycle 2 by 93.75% (30 people). These results indicate that the use of wordwall learning media can increase students' interest in learning Civics in class VI of SD Inpres 3 Tondo.